A new species and a new combination in the genus Aureoboletus (Boletales, Boletaceae) from southern China - Zeng, Nian-Kai; Zhang, Ming; Liang, Zhi-Qun (Phytotaxa, 2015)
Two lineages of Aureoboletus (Boletales, Boletaceae) from southern China were revealed by using molecular data based on combined dataset of the nuclear ribosomal large subunit RNA (nrLSU), the translation elongation factor apha-1 (tef1-a) and the largest subunit of RNA polymerase II (rpb1). One of them corresponds with the previous morphology-based taxon, viz. Boletellus longicollis, another one is different from those taxa described based on morphological features. And, thus, Auroboletus clavatus sp. nov. and A. longicollis comb. nov. were proposed. A detailed description, colour photos of fresh basidiomata, and a line-drawing of microscopic features of the two taxa were provided.